IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXTS THROUGH EXPERIENCE TEXT RELATIONSHIP (ETR) METHOD AT SMA SWASTA PALAPA MEDAN IN THE ACADEMIC YEAR OF 2020/2021 - Lahagu, Yatafati; Pangaribuan, Jontra Jusat; Prayuda, Meikardo Samuel (Kairos English Language Teaching Journal, 2021)
This research was conducted in order to improve students’ Reading Comprehension on Narrative Texts through ETR method and to know the students’ responses towards the learning reading comprehension through ETR method at SMA Swasta Palapa Medan. In conducting this research, the writer used Classroom Action Research (CAR). This research showed that teaching reading comprehension through ETR method at SMA Swasta Palapa Medan could improve their reading comprehension. The result of the test showed that the students’ mean score in pre-test is 51.59 with 4 students (13,79%) of the students got score ≥70, in formative test the mean score is 68.69 with 15 students (51,72%) of the students got score ≥70, and in post-test the mean score is 77.66 with 21 students (72,41%) of the students got score ≥70. The writer concluded that ETR method could improve the eleventh grade students’ reading comprehension on narrative texts of SMA Swasta Palapa Medan. On the other hand, the students’ responses towards the method of the teaching sound good because above 80% of the students are interested, motivated and understand the lesson with the ETR method.